Hubungan Citra Destinasi Wisata dengan Frekuensi Kedatangan Wisatawan Global di Kota Padang - Neni Efrita (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Eart region of tour destination has a certain image types,with are mental maps of someone about containing the destination beliefs, impressions and perceptions. The image of a tourist destination will also affect the tourists to take a decision to travel, this is one of the factors driving or towing. Real push and pull factors are internal factors and ekstrenal what motivates people to make decisions for the leisure traveler. This paper describes the relationship of the image of a tourist destination with a frequency of global tourist arrivals in West Sumatra